2017
DOI: 10.1016/j.neuroimage.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Towards person-centered neuroimaging markers for resilience and vulnerability in Bipolar Disorder

Abstract: Improved clinical care for Bipolar Disorder (BD) relies on the identification of diagnostic markers that can reliably detect disease-related signals in clinically heterogeneous populations. At the very least, diagnostic markers should be able to differentiate patients with BD from healthy individuals and from individuals at familial risk for BD who either remain well or develop other psychopathology, most commonly Major Depressive Disorder (MDD). These issues are particularly pertinent to the development of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Eight functional studies were found, 1 used arterial spin labelling (ASL) of anterior cingulate cortex reaching 52.8% ACC, 55 3 used resting‐state fMRI reaching between 61.7, 56 81% 57 and 82.22% ACC 58 and 4 used task‐based fMRI reaching between 59.72% and 83.5% ACC 59‐62 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Eight functional studies were found, 1 used arterial spin labelling (ASL) of anterior cingulate cortex reaching 52.8% ACC, 55 3 used resting‐state fMRI reaching between 61.7, 56 81% 57 and 82.22% ACC 58 and 4 used task‐based fMRI reaching between 59.72% and 83.5% ACC 59‐62 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Next multivariate machine learning was applied to investigate the individual-level classification accuracy of the Go-No-go task for subjects in each group (Frangou, Dima et al 2017).…”
Section: Cha Page 14mentioning
confidence: 99%
“…Although several studies have used close relatives of bipolar subjects to identify high risk endophenotypes (Piguet, Fodoulian et al 2015, Vierck, Porter et al 2015, Frangou, Dima et al 2017), MDD+ subjects have not yet been used to identify clinically applicable activation patterns, with the ultimate goal of applying these patterns in clinical work to identify at-risk individuals.…”
mentioning
confidence: 99%
See 2 more Smart Citations